Arte, arquitetura e cultura: caminhos para a resistência na obra de Lina Bo Bardi e de Hélio Oiticica - Aleixo, Paulo Arthur Silva (2020)
In the vibrant Brazilian cultural production of the 1950s and 1960s, the approximation between the ideals of different fields of expression was common. This was a time when professionals in the arts and architecture were interested in moving out of their narrow spheres, taking a political stand by rethinking cultural production, aiming to strengthen the relationship with the popular strata and change the established situation. However, the 1964 coup d’état, which created a state of tension in the country's politics and culture, frustrated much of this artistic production, forcing the current thinkers to reorganize and rethink their acting strategies in the face of complicated reality established. In this scenario, the names of the Italian-Brazilian architect Lina Bo Bardi (Rome, 1914 - São Paulo, 1992) and the artist Hélio Oiticica (Rio de Janeiro, 1937 - Rio de Janeiro, 1980) are protagonists in the construction of a thought that sought, above all, ways to question the status quo and transform society. Acting in different places - Bo Bardi between Bahia and São Paulo, Oiticica between Rio de Janeiro and New York - and belonging to different generations and fields of production, their trajectories never crossed, despite having a strong affinity of convictions. The interventions of these figures have condensed but also served as a starting point for most of the concerns contained in the reflections of contemporary architects, artists and intellectuals. Thus, the present work seeks to initiate a reflection on the principles and vital interlocutions that Bo Bardi and Oiticica nurtured in the passage from the 1960s to the 1970s, trying to understand how their productions stood as voices of resistance to the established. To this end, it starts from successive approaches, isolating some influential figures and certain activities developed that, placed in the same perspective, can contribute to the image of a potent cultural phenomenon that fought for greater social and political engagement.